DEVELOPMENT AND EVALUATION OF IN-SITU GELLING OTIC FORMULATIONS OF AZITHROMYCIN DIHYDRATE USING POLOXAMER - S. A. SHARMA; S. V. SHIROLKAR (The Bioscan, 2012)
Azithromycin dihydrate has been indicated in the treatment of chronic suppurative otitis media (CSOM). The aim of this study was to develop in situ gel forming ear drops of Azithromycin dihydrate. 1% w/v azithromycin dihydrate otic solution and in situ gel forming otic solutions were prepared. Poloxamer 407 forms thermoreversible gels so it was used as in situ gelling agent. Poloxamer concentration in the range of 15-20% w/v was tried. 18 and 19% w/v Poloxamer 407 gave satisfactory in situ gel forming formulations. Poloxamer 407 with viscosity increasing agents like Methocel K100M Premium and Carbopol 974 were also tried in range of 0.2-2% w/v. The formulations were evaluated for appearance/clarity, gelling time, pH, rheological characteristic and in vitro diffusion through synthetic membrane. The viscosity of formulations increased as concentration of Poloxamer 407 increased. When Poloxamer 407 concentration was kept constant, viscosity of formulations increased with increasing concentration of HPMC K4M and Cabopol 974. In vitro release from synthetic membrane showed that in situ gelling formulations were releasing the drug slowly as compared to drug solution. In case of ear drops, the drug released was more than 90% in 3h and from in situ gel formulation, drug released was less than 40% in 3h. From in situ gel formulations drug release was sustained upto 8h. Thus in situ gelling formulations are likely to give patient convenience and reduce frequency of ear drops administration.